Valorization of Tomato By-Products: Advanced Extraction Methods and Bioprocessing of Bioactive Compounds and Functional Products - Christina Drosou; Konstantina Theodora Laina; Maria Dimoula; Panagiota Maria Eleni; Christos J. Boukouvalas; Evangelos Topakas; Magdalini Krokida (Applied Sciences)
This study investigates the valorization of tomato by-products—peels, seeds, and juice—through innovative extraction and bioprocessing techniques. Lycopene recovery from tomato peels was optimized using ultrasound- and microwave-assisted extraction (UAE-MAE) with ethyl lactate as the solvent. The optimal conditions (0.03 g/mL, 500 W microwave power, 600 W ultrasound power) yielded a lycopene content of 37.08 mg/100 g of peels and an extraction yield (EY) of 91.20%. For tomato seeds, oil extraction methods, including conventional stirring, UAE-MAE, Soxhlet extraction, and pressurized liquid extraction (PLE), were evaluated. Conventional stirring achieved the highest oil yield (19.66%), followed closely by UAE-MAE (19.53%). However, PLE produced the highest lycopene content (44.0 mg/100 g oil) and significant levels of linoleic acid (544.7 mg/g oil), though Soxhlet extraction yielded slightly more (608.9 mg/g oil). Tomato juice was processed into high-nutritional value vinegar via a two-stage fermentation process. The final product had 5.42% acidity, a pH of 2.85, and retained a high lycopene content (9.19 mg/100 g). This study underscores the potential of innovative extraction and bioprocessing strategies for the valorization of tomato by-products, promoting waste reduction and the development of high-value functional products in alignment with principles of the circular bioeconomy.